NMR studies of the polyphotochromic behaviour of biphotochromic compounds - J. Berthet; S. Delbaere; V. Lokshin; A. Samat; J. C. Micheau; G. Vermeersch (International Journal of Photoenergy)
NMR spectroscopy has been used to investigate the photochromism of four biphotochromic molecules in both the spirooxazine and naphthopyran families. The thermal evolution of photoproducts and their structural identification made it possible to observe polyphotochromic behaviour: photocoloration, thermal bleaching, photo and thermal isomerisation, photoelectrocyclisation and thermochromism.